O idoso encarcerado : considerações criminológicas - Ghiggi, Marina Portella (2012)
Aiming to demonstrate that the ageing population, as one of the most remarkable features of the present time, brings on miscellaneous social modifications, requiring approaches in all areas of the knowledge, this thesis for master s degree, linked to the Criminology and Social Control s line of research from the Pos-Graduation Program in Criminal Science of the Pontificia Universidade Catolica do Rio Grande do Sul, has as its primordial goal to present specifically the elderly people involved with the criminal justice system and imprisonment. In these terms, taking into consideration the aging peculiarities, an approach based on the gerontology initiates this study, featuring the main characteristics and the implications of the ageing population, the elderly person s role throughout the centuries, as well as the studies on aging. To set the context of the elderly person in the Brazilian law, part of this work is dedicated to the analysis of the treatment given by Brazilian legislation to the elderly person. In order to illustrate the situation mentioned, some of the criminal judgments, where the defendants are elderly people, are analyzed. The next approach is exactly about the elderly person inserted in the justice system, presenting an overview of the elderly person in prison in Brazil as well as considerations about the ageing inside a prison and the physical violence on the elderly person s body. In conclusion, as the justice system is responsible for irreparable degradations, it is imperative that initiatives should be aimed firstly and mainly to prevent their involvement with the justice system and, in case that this is not possible, to better direct the prisons to the precepts dictated by the human rights which should be held also by the involved elderly person s view. It is believed that it is mainly through the Criminology and the Gerontology that alternatives to this situation should be sought.